Analysis and Design for Networked Teleoperation System - Hua, Changchun; Yang, Yana.; Yang, Xian.; Guan, Xinping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents cutting-edge results on stability analysis and control scheme designs for networked teleoperation systems. It highlights new research on commonly encountered nonlinear teleoperation systems, including the stability analysis of teleoperation systems with asymmetric time-varying delays, stability analysis of teleoperation systems with interval time delays, and so on. Moreover, the book presents several high-performance control scheme designs for teleoperation systems when the velocity is available and unavailable, and for systems with nonlinear input. The results presented here mark a substantial contribution to nonlinear teleoperation system theory, robotic control theory and networked control system theory. As such, the book will be of interest to university researchers, R&D engineers and graduate students in control theory and control engineering who wish to learn about the core principles, methods, algorithms, and applications of networked teleoperation systems, robotic systems and nonlinear control systems.
Introduction -- Convergence Analysis of Teleoperation Systems With Unsymmetrical Time-Varying Delays -- Stability Analysis of Teleoperation Systems With Asymmetric Time-Varying Delays -- Stability Analysis of Teleoperation Systems withAsymmetric Interval Time-Varying Delays -- Stability Analysis of Teleoperation Systems with Quantization -- Directed Force Feedback Control Design with Asymmetric and Time-varying Delays -- Teleoperation over the Internet with exponential convergence -- Finite Time Controller Design -- Constrained Control Design for Bilateral Teleoperation System -- Output Feedback Controller Design for Teleoperation System via High-gain Observer -- Finite Time Observer Design for Teleoperation System -- On Exploring the Domain of Attraction for Bilateral Teleoperator -- Adaptive Controller Design for Teleoperation System With Actuator Saturation. .
Keywords: Control engineering; Robotics; Automation; Telecommunication; System theory; Control theory; Control and Systems Theory; Control, Robotics, Automation; Communications Engineering, Networks; Systems Theory, Control